2010
DOI: 10.1111/j.1471-4159.2010.06962.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Synuclein expression is induced by depolarization and cyclic AMP in enteric neurons

Abstract: Accumulated evidence emphasizes the importance of α-synuclein expression levels in Parkinson's disease (PD) pathogenesis. PD is a multicentric disorder that affects the enteric nervous system (ENS), whose involvement may herald the degenerative process in the CNS. We therefore undertook the present study to investigate the mechanisms involved in the regulation of expression of α-synuclein in the ENS. The regulation of α-synuclein expression was assessed by qPCR and western blot analysis in rat primary culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…In the latter case, a signaling pathway involving ERK/PI3 kinase signaling mediated ZSCAN-induced SNCA transcriptional activation (Clough and Stefanis 2007;Clough et al 2009). A similar ERK-dependent signaling pathway regulating SNCA production was apparent in enteric neurons (Paillusson et al 2010). Methylation may be important in SNCA expression, as methylation within Intron 1 suppressed SNCA transcriptional activity, and brains of patients with LB diseases showed decreased methylation within this region, suggesting epigenetic regulation of SNCA expression (Jowaed et al 2010;Matsumoto et al 2010).…”
Section: Gain-of-function and Accumulation Of A-synucleinmentioning
confidence: 81%
“…In the latter case, a signaling pathway involving ERK/PI3 kinase signaling mediated ZSCAN-induced SNCA transcriptional activation (Clough and Stefanis 2007;Clough et al 2009). A similar ERK-dependent signaling pathway regulating SNCA production was apparent in enteric neurons (Paillusson et al 2010). Methylation may be important in SNCA expression, as methylation within Intron 1 suppressed SNCA transcriptional activity, and brains of patients with LB diseases showed decreased methylation within this region, suggesting epigenetic regulation of SNCA expression (Jowaed et al 2010;Matsumoto et al 2010).…”
Section: Gain-of-function and Accumulation Of A-synucleinmentioning
confidence: 81%
“…In a more general consideration, ERK is known to be activated in response to stimuli linked to neuronal activity [43]. However, it is also well known that the activation of MAPK is transient [43,44] and hardly ever sustained in physiological conditions, due to desensitizing or negative feedback processes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also well known that the activation of MAPK is transient [43,44] and hardly ever sustained in physiological conditions, due to desensitizing or negative feedback processes. We could assume that ENS activation precociously activates ERK pathways that might not be further impacted by LPS stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which environmental agents induce α-synuclein aggregation is unknown. However, a recent study showed that α-synuclein expression in the ENS could be upregulated by agents that cause depolarization and increase the levels of cyclic AMP [24]. …”
Section: Discussionmentioning
confidence: 99%